Autonomic changes induced by pre-competitive stress in cyclists in relation to physical fitness and anxiet - Oliveira-Silva, I.; Silva, V. A.; Cunha, R. M.; Foster, C. (PLOS ONE, 2018)
Cycling is a sport which requires great physical effort from athletes. The stress and anxiety of competition might interfere greatly with performance, by impacting the autonomic system. Physiological alterations, such as situations that irritate, frighten or excite the individual can cause a stress response, defined as a response of the organism to reestablish the homeostasis, regardless of its relationship to a sports situation. The aim of this study was to present data on the autonomic changes induced by precompetitive stress in cyclists and their relation with physical fitness and anxiety. Twelve healthy cyclists aged between 18 and 40 years, with previous experience in competition at the regional level, participated in the study. Heart rate variability (HRV) and physical fitness (body mass index, body fat and aerobic capacity) were measured 5 days before the Mountain Bike championship and remeasured 45 minutes before the start of the race (HRV and Anciety). Paired T test, effect size and correlational test were used. Cycling competition is a stressful situation capable of altering autonomic and hemodynamic parameters. We observed the increase in SDNN, reflecting an increase in sympathetic autonomic control. There were correlations between physical fitness with some autonomic parameters, while anxiety correlated with the years of experience in competition.